2021
DOI: 10.3390/cancers13164207
|View full text |Cite
|
Sign up to set email alerts
|

Computational Approaches for Cancer-Fighting: From Gene Expression to Functional Foods

Abstract: It is today widely accepted that a healthy diet is very useful to prevent the risk for cancer or its deleterious effects. Nutrigenomics studies are therefore taking place with the aim to test the effects of nutrients at molecular level and contribute to the search for anti-cancer treatments. These efforts are expanding the precious source of information necessary for the selection of natural compounds useful for the design of novel drugs or functional foods. Here we present a computational study to select new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 142 publications
0
4
0
Order By: Relevance
“…The early symptoms of this cancer are very subtle or lacking, so it is often diagnosed after the disease has deteriorated significantly, which makes the early diagnosis rate only 1.43%. With the development of bioinformatics, transcriptomic studies have found that some genes involved in tumorigenesis and metastasis are differentially expressed in tumor and normal tissues [72][73][74][75]. This opens the possibility for early detection of esophageal squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…The early symptoms of this cancer are very subtle or lacking, so it is often diagnosed after the disease has deteriorated significantly, which makes the early diagnosis rate only 1.43%. With the development of bioinformatics, transcriptomic studies have found that some genes involved in tumorigenesis and metastasis are differentially expressed in tumor and normal tissues [72][73][74][75]. This opens the possibility for early detection of esophageal squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…* sı Supporting Information ABSTRACT: An approach for the construction of the tricyclic framework of naturally occurring cyclocalopin A is described. The establishment of the crucial intermediate α-methylene bis-γ,δlactone involves a [2 + 2 + 1]-cyclocarbonylation of newly introduced allenyl glyoxylate via direct methods using Mo(CO) 6 or sequential reaction pathways. The sequential reaction route involved a stannylative cyclization by Pd(0) catalyst, bromination of an vinyl stannane moiety, and final cyclocarbonylation by palladium catalysis to provide the bis-γ,δ-lactone.…”
mentioning
confidence: 99%
“…Cyclocalopin shows potent free-radicalscavenging activity against superoxide, DPPH, and ABTS radicals with IC 50 values of 1.2−5.4 μg/mL and recently anticancer activities against several cell lines. 4,6 More than 20 types of cyclocalopin families have been discovered, with diverse structures such as cyclocalopin A (fused bicyclic with spiro-ring), cyclocalopin E (fused and bridged four rings), and isocyclocalopin A (bridged bicyclic rings with spiro-unit). Nonetheless, all cyclocalopin family natural products were closely related each other by simple chemical and biological conversions as described in Scheme 1.…”
mentioning
confidence: 99%
See 1 more Smart Citation